Emergence of KPC-2 and NDM-5-coproducing hypervirulent carbapenem-resistant Klebsiella pneumoniae with high-risk sequence types ST11 and ST15 - Ying Zhou; Xiaocui Wu; Chunyang Wu; Peiyao Zhou; Yang Yang; Bingjie Wang; Yanlei Xu; Huilin Zhao; Yinjuan Guo; Jingyi Yu; Fangyou Yu (2024)
ABSTRACT The emergence of Klebsiella pneumoniae carbapenemase-2 (KPC-2) and New Delhi metallo-β-lactamase (NDM)-coproducing hypervirulent carbapenem-resistant Klebsiella pneumoniae (KPC-2-NDM-hv-CRKP) poses a certain threat to public health. Currently, only a few sporadic reports of such double-positive hv-CRKPs were available. In this study, we isolated two KPC-2-NDM-5-hv-CRKPs from elderly patients with serious underlying diseases and poor prognoses. We found both FK3122 and FK3127 were typical multidrug-resistant (MDR) isolates, exhibiting high-level resistance to both carbapenems and novel β-lactamase inhibitors ceftazidime/avibactam. Notably, FK3122 is even resistant to cefiderocol due to multiple bla NDM-5 elements. Besides the MDR phenotype, A549 human lung epithelial cells and Galleria mellonella infection model all indicated that FK3122 and FK3127 were highly pathogenic. According to the whole-genome sequencing analysis, we observed over 10 resistant elements, and the uncommon co-existence of bla KPC-2 , bla NDM-5 , and virulence plasmids in both two isolates. Both virulence plasmids identified in FK3122 and FK3127 shared a high identity with classical virulence plasmid pK2044, harboring specific hypervirulent factors: rmpA and iuc operon. We also found that the resistance and virulence plasmids in FK3127 could not only be transferred to Escherichia coli EC600 independently but also together as a co-transfer, which was additionally confirmed by the S1-pulsed-field gel electrophoresis plasmid profile. Moreover, polymorphic mobile genetic elements were found surrounding resistance genes, which may stimulate the mobilization of resistance genes and result in the duplication of these elements. Considering the combination of high pathogenicity, limited therapy options, and easy transmission of KPC-2-NDM-5-hv-CRKP, our study emphasizes the need for underscores the imperative for ongoing surveillance of these pathogens. IMPORTANCE Hypervirulent Klebsiella pneumoniae drug resistance has increased gradually with the emergence of carbapenem-resistant hypervirulent K. pneumoniae (hv-CRKP). However, little information is available on the virulence characteristics of the New Delhi metallo-β-lactamase (NDM) and Klebsiella pneumoniae carbapenemase-2 (KPC-2) co-producing K. pneumoniae strains. In this study, we obtained two KPC-2-NDM-hv-CRKPs from elderly patients, each with distinct capsule types and sequence types: ST11-KL64 and ST15-KL24; these ST-type lineages are recognized as classical multidrug-resistant (MDR) K. pneumoniae . We found these KPC-2-NDM-hv-CRKPs were not only typical MDR isolates, including resistance to ceftazidime/avibactam and cefiderocol, but also displayed exceptionally high levels of pathogenicity. In addition, these high-risk factors can also be transferred to other isolates. Consequently, our study underscores the need for ongoing surveillance of these isolates due to their heightened pathogenicity, limited therapeutic options, and potential for easy transmission.